Proton magnetic resonance spectroscopy changes after lithium treatment. Systematic review. (30th March 2018) - Szulc, Agata; Wiedlocha, Magdalena; Waszkiewicz, Napoleon; Galińska-Skok, Beata; Marcinowicz, Piotr; Gierus, Jacek; Mosiolek, Anna
Abstract: 1H MRS is widely used in the research of mental disorders. It enables evaluation of concentration or ratios of several metabolites, which play important roles in brain metabolism: N-acetylaspartate (NAA), choline containing compounds, myo-inositol and glutamate, glutamine and GABA (together as Glx complex or separately). Specifically in bipolar disorder brain metabolite abnormalities include mostly NAA reduces and Glx increases in different brain regions. Bipolar disorder is associated with impairment in neurotrophic and cellular plasticity, resilience pathways and in neuroprotective processes. Lithium, which is commonly used in BD treatment, modulates neurotransmitter release, reduces oxidative stress and apoptosis, induces angiogenesis, neurogenesis and neurotrophic response. Thus brain metabolite abnormalities may elucidate the mechanisms of this processes. In the present article we systematically reviewed 26 studies - the majority of them investigated bipolar disorder ( 7 follow-up and all 11 cross-sectional studies). Moreover we dispute whether the influence of lithium on brain metabolites in bipolar disorder could explain the background of its potential neuroprotective action. The results of our literature review do not equivocally confirm Lithium's influence the metabolite changes in the brain. The majority of the follow-up studies do not support the initially assumed influence of Lithium on the increase of NAA level in various brain structures. The results of studies are inconclusive with regard to levels of Glx or Glu and Lithium intake, rather point a lack of relationship. The above results were reviewed according to the most recent theories in the field accounting for the impact of lithium (1)HMRS measures.